2008
DOI: 10.1093/ajcn/87.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a high-protein ketogenic diet on hunger, appetite, and weight loss in obese men feeding ad libitum

Abstract: In the short term, high-protein, low-carbohydrate ketogenic diets reduce hunger and lower food intake significantly more than do high-protein, medium-carbohydrate nonketogenic diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
281
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(304 citation statements)
references
References 58 publications
(73 reference statements)
15
281
2
6
Order By: Relevance
“…These results were similar to other reporting data from four weeks of intervention 23 . However, it is typically observed that a CRD promotes higher reductions in triacylglycerol and increases in HDL-c levels compared to conventional diets 22,25 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results were similar to other reporting data from four weeks of intervention 23 . However, it is typically observed that a CRD promotes higher reductions in triacylglycerol and increases in HDL-c levels compared to conventional diets 22,25 .…”
Section: Discussionsupporting
confidence: 93%
“…Johnstone et al 23 reported that four weeks of non-ketogenic CRD (approximately 35% of total energy from carbohydrate) led to a significantly lower body mass loss (-4.4 kg versus -6.3 kg) than Analyses of individual cases showed that 2/7 subjects in the CRD group and 3/7 in the conventional diet group had low baseline FMD values. At the end of intervention, one subject in each group had improved FMD values.…”
Section: Tc/hdl-c Ratiomentioning
confidence: 99%
“…There has been a considerable utilisation of lowcarbohydrate diets, in which the protein component is conspicuous (8,9) , but most of the discussion of their effects has been centred on their ketogenic (i.e. lipid, absence of carbohydrate) nature (10) , the amino acids essentially being considered potential gluconeogenic substrates (11) , with little impact on protein synthesis (12) .…”
Section: Introductionmentioning
confidence: 99%
“…lipid, absence of carbohydrate) nature (10) , the amino acids essentially being considered potential gluconeogenic substrates (11) , with little impact on protein synthesis (12) . More recently, the use of hyperproteic diets (13) is again on the rise, but we still lack the necessary basic knowledge to interpret the results obtained, largely because of few systematic analyses and the continued stress on their ketogenic nature (8,9) . However, under conditions of abundant food supply, the main question is not how amino acids fare under conditions of low energy availability, but the contrary: how the metabolic machinery can override the strong protective mechanisms preventing N wasting under conditions of excess energy (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Diet design or food reformulation that makes use of, for example, differentially satiating macronutrients or specific components that target aspects of the satiety cascade (12)(13)(14)(15) have been shown in experimental settings to support both weight loss (20)(21) and weight maintenance after weight loss (22) . Crucially, these outcomes can be achieved under ad libitum feeding conditions.…”
Section: Obesity Treatmentmentioning
confidence: 99%